The ANALYSIS OF INDONESIAN LANGUAGE TEACHERS’ PROFESSIONALISM IN CURRICULUM IMPLEMENTATION: A COMPARATIVE STUDY WITH TEACHER PROFESSIONALISM STANDARDS IN SINGAPOREAN CURRICULUM - Risma Fitriyani; Rizkia Mulyani; Siti Maulida; Decinta Nesa Karisma (Cakrawala Pedagogik, 2025)
This study aims to analyze the professionalism of Indonesian language teachers in implementing the Merdeka Curriculum in class XI at SMAN 1 Bojonegara and compare it with the standards of teacher professionalism in Singapore. The research used a descriptive qualitative approach through observation and interviews with Indonesian language teachers. The results showed that teachers had demonstrated professionalism through lesson planning based on the curriculum, adjusting materials to student needs, using relevant learning strategies, managing classrooms effectively, and implementing routine reflection and evaluation. However, when compared to Singaporean standards, teacher professionalism still differs, especially in the aspects of learning differentiation, continuous professional development, and structured institutional support. These findings indicate that teachers are on the right track but still require continuous support to optimize their professional practices.